Báo cáo tổng hợp ý kiến, kiến nghị của cử tri và Nhân dân (Tại kỳ họp thứ 11 Quốc hội khóa XIV) (Số: 309/BC-MTTW-ĐCT) - Đoàn chủ tịch- UBMTTQ (2021)
Toàn văn Báo cáo tổng hợp ý kiến, kiến nghị của cử tri và Nhân dân (Tại kỳ họp thứ 11 Quốc hội khóa XIV) (Số: 309/BC-MTTW-ĐCT)